The effect of sodium-glucose cotransporter 2 inhibitors on biomarkers of inflammation: A systematic review and meta-analysis of randomized controlled trials - Wang, Dongmei; Liu, Jieying; Zhong, Ling; Li, Shunhua; Zhou, Liyuan; Zhang, Qian; Li, Ming; Xiao, Xinhua (Frontiers in Pharmacology, 2022)
Aims: Inflammatory biomarkers may play vital roles in the pathophysiology of diabetes and diabetic cardiorenal complications. Sodium-glucose cotransporter-2 (SGLT2) inhibitors have a potential cardiovascular and renal protective effect in type 2 diabetes. The aim of this meta-analysis was to quantify the effects of SGLT2 inhibitors on biomarkers of inflammation in randomized controlled trials (RCTs). Methods: PubMed, Cochrane Library, EMBASE and Web of Science were searched for eligible RCTs in adults with type 2 diabetes (T2D) without any time limit (updated to October 12th, 2022). The biomarkers selected included C-reactive protein (CRP), interleukin-6, tumor necrosis factor-alpha, leptin, adiponectin, ferritin, plasminogen activator inhibitor (PAI)-1 and vascular cell adhesion molecule-1. Data were analyzed using a random-effect model by Review Manager 5.4. Results: Thirty-four studies with 6,261 patients (68.6% male) were eligible for this meta-analysis. The mean age of the participants was 62.57(±11.13) years old, and the median treatment duration length of follow-up was 24 weeks. Generally, the included trials were of good methodological quality. Meta-analysis revealed that ferritin levels were significantly reduced in SGLT2 inhibitor treatment groups versus placebo or standard diabetes therapies (SMD: -1.21; 95% CI: -1.91, -0.52, P ＜ 0.001). The reduced effects of CRP (SMD: -0.25; 95% CI: -0.47, -0.03, P = 0.02), leptin (SMD: -0.22; 95% CI: -0.43, -0.01, P = 0.04) and improving effects of adiponectin (SMD: 0.28; 95% CI: 0.15, 0.41, P ＜ 0.001) were demonstrated in placebo-controlled studies. PAI-1 levels were significantly reduced in diabetes therapies-controlled studies (SMD: -0.38; 95% CI: -0.61, -0.15, P = 0.001). Conclusions: This analysis provides strong evidence supporting the anti-inflammatory effects of SGLT2 inhibitors in T2D subjects. Inflammation-related mechanisms and possible targets for the cardiorenal protective properties of SGLT2 inhibitors remain to be explored.